A Service Oriented Framework for Natural Language Text Enrichment - Štajner, T.; Rusu, D.; Dali, L.; Fortuna, B.; Mladenić, D.; Grobelnik, M. (Informatica)
A Service Oriented Framework for Natural Language Text Enrichment